School Contribution to the Community in the Implementation of Vocational High School Empowering Village Program in Kalibawang Sub-District of Wonosobo - Muhammad Sayuti; Edhy Susatya; Riyadi Riyadi (Journal of Vocational Education Studies, 2022)
The objectives of this study are (1) to analyze the contribution of SMK Negeri 1 Kalibawang in efforts to empower the village community of Kalibawang District through the implementation of the 'SMK Membangun Desa' program; (2) analyze the factors supporting the contribution of SMK in efforts to empower the village community of Kalibawang District in the implementation of the 'SMK Membangun Desa' program; (3) analyze the inhibiting factorsfor smk's contribution in efforts to empower the village community of Kalibawang District in the implementation of the 'SMK Membangun Desa' program. The research uses a qualitative approach with phenomenological strategies in the implementation of the 'SMK Membangun Desa' program. The research was carried out at SMK Negeri 1 Kalibawang and the Kalibawang District Government. Data collection is carried out by interview, observation, and documentation techniques. Data analysis and validation using source triangulation techniques. The results showed that (1) the implementation of the 'SMK Membangun Desa' program is able to contribute to the improvement of human resources (HR) of the community and the economy of the Kalibawang community through community empowerment strategy-based activities that are integrated with the needs in the village and become one of the solutions to improve the competence of students in the industrial world and theproductivity of students, including: career center on each competency of expertise (Motorcycle Engineering and Business, Accounting and Financial Institutions, Computer and Network Engineering), banana cultivation on SMK land, entrepreneur e-workshop training, marketing of home industry products, promotion of tourist village destinations, community service, sharing public health, and launching program 'SMK Building Villages towards superior smk based on empowerment. (2) supporting factors in the implementation of the 'SMK Membangun Desa' program are the support of the village government, the ability of competent vocational schools, adequate infrastructure and facilities, and the commitment of all SMK residents. (3) inhibiting factors in the implementation of the 'SMK Membangun Desa' program regarding time constraints that arethe same as the Coronavirus Disease 2019 pandemic, and program fundingcan be andmanaged independently because it is not a program assistance from the government.